Exploring the Interpretation of the Verses of Meritocracy in the Qur'an: Abdullah Saeed's Contextual Approach - M Irsyad Muhyiddin Abdul Haq; Muhammad Irsad; Muhammad Nur Amin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Meritocracy is a system of placing individuals in positions or roles based on ability, achievement, and worthiness, not because of kinship, social status, or certain interests. This study aims to explore the interpretation of meritocratic verses in the Qur'an through Abdullah Saeed's contextual interpretation approach and analyze their relevance to the contemporary meritocratic leadership system. This study uses a qualitative method with a library research type. Primary data are in the form of Qur'anic verses related to meritocracy, while secondary data are obtained from Abdullah Saeed's works, tafsir books, books, journals, and relevant academic studies. Data analysis is carried out descriptively-analytically through Abdullah Saeed's four steps of contextual interpretation. The results of the study indicate that meritocracy in the Qur'an does not only emphasize ability and achievement, but also integrity, character, empathy, and moral responsibility. QS Al-Qasas [28]: 26 emphasizes competence and trustworthiness, QS Al-Isra’ [17]:84 emphasizes the suitability of roles to individual character, and QS At-Taubah [9]:128 presents a model of empathetic and compassionate leadership. Thus, meritocracy from the perspective of the Qur’an offers a leadership paradigm that is holistic, ethical, and relevant to contemporary organizational and governmental governance.